Long-term outcomes of mitral valve repair in children - Tuncer, Osman Nuri; Ertugay, Serkan; Akhundova, Mahsati; Levent, Ertürk; Atay, Yüksel (Frontiers in Cardiovascular Medicine, 2024)
BACKGROUNDː Mitral Valve Disease in children presents unique challenges due to the wide range of associated pathologies and the complexities of pediatric cardiac anatomy. Mitral valve repair in this demographic is preferred over replacement due to the drawbacks associated with prosthetic valves in young patients, such as the need for longterm anticoagulation and issues with prosthetic size and growth METHODSː This retrospective study reviewed pediatric patients under 18 years who underwent mitral valve repair between January 2002 and December 2023. Exclusion criteria included patients with atrioventricular septal defects or single-ventricle physiology. Surgical outcomes were assessed using preoperative and postoperative transthoracic echocardiography, with follow-up data analyzed via Kaplan-Meier survival estimates RESULTSː The study included 47 patients with a median age of 4 years. Surgical techniques varied based on the specific mitral valve pathology. The overall early mortality was 6.3%, and the one and ten-year survival rates were 93.6±3.6% and 91.4±4.1%, respectively. Most patients showed improved or stable postoperative cardiac function during a median follow-up of 105 months. Notably, the rate of freedom from re-operation at ten years was 85.1±6.9%, highlighting the durability of the surgical interventions.CONCLUSIONSː Mitral valve repair in children demonstrates favorable long-term outcomes with low mortality and reoperation rates, particularly when performed at an older age to accommodate growth and avoid the complexities of smaller, more delicate cardiac structures. These findings suggest that mitral valve repair should be considered a viable and effective option for managing pediatric MVD, with a personalized approach essential for optimizing outcomes.